1979
DOI: 10.3109/01485017908988418
|View full text |Cite
|
Sign up to set email alerts
|

Anatomy of the Human Seminal Vesicles and Ejaculatory Ducts

Abstract: Anatomical dissections of the seminal vesicles and ejaculatory ducts were carried out in 20 autopsy and 10 operative specimens. Seminal vesiculography and casting were made. Vesiculography was conducted on 50 cases of schistosomal seminal vesiculitis. The seminal vesicles were of variable size and three main anatomical types. In normal seminal vesicles the ampullary vesicular angle was acute and the average length of the ejaculatory duct was 2.2 mm with an antero-medial concavity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 4 publications
0
16
0
Order By: Relevance
“…Several studies have described the normal size range of the seminal vesicles using gross anatomical measurements or by transrectal ultrasonography, CT, or magnetic resonance imaging (MRI). Using gross anatomy, Aboul‐Azm () reported that the mean length of the seminal vesicles was 50 ± 0.9 mm and the mean thickness 12 ± 0.2 mm. Hoekstra et al () used transrectal ultrasonography and reported that the mean width of the seminal vesicles was 9.7 mm on the right side and 9.3 mm on the left.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have described the normal size range of the seminal vesicles using gross anatomical measurements or by transrectal ultrasonography, CT, or magnetic resonance imaging (MRI). Using gross anatomy, Aboul‐Azm () reported that the mean length of the seminal vesicles was 50 ± 0.9 mm and the mean thickness 12 ± 0.2 mm. Hoekstra et al () used transrectal ultrasonography and reported that the mean width of the seminal vesicles was 9.7 mm on the right side and 9.3 mm on the left.…”
Section: Discussionmentioning
confidence: 99%
“…A study of cadaveric and surgical specimens by Nguyen et al () at the University of California School of Medicine, San Francisco, USA found that the thick muscle walls of the seminal vesicles are absent in the ejaculatory duct and normal duct dimensions are remarkably uniform among U.S. men. Aboul‐Azm () found that the ampullary vesicular angle of the ejaculatory duct was acute and the duct had anteromedial concavity. Nguyen et al () studied 10 cadaveric prostates and 10 prostates obtained after radical prostatectomy and revealed that ejaculatory ducts course obliquely toward each other as they proceed toward the seminal colliculus.…”
Section: Introductionmentioning
confidence: 99%
“…In this study of specimens obtained by robotic-assisted laparoscopic dissections, a wide range of seminal vesicle lengths was found (8.5-94.6 mm), much larger than the range reported in autopsies (20-60 mm) [1,2], seminal vesiculograms (27-66 mm) [4], plastic corrosion models (17-59 mm) [3] and transrectal sonography (22-56 mm) [5]. We may attribute this diVerence to the higher pliability of living tissues as compared to corpses, and to the accuracy of trans-peritoneal robotic-assisted dissections even with extremely long seminal vesicles.…”
Section: Discussionmentioning
confidence: 48%
“…Traditional studies in seminal vesicle anatomy employed dissection of fresh and preserved corpses, seminal vesiculograms and transrectal sonography [1][2][3][4][5][6]. Based on autopsies of 161 men, Calams showed that this is a symmetric organ with a length of 2-5.8 cm.…”
Section: Introductionmentioning
confidence: 99%